KOMUNIKASI ASERTIF ANAK DENGAN KEDISABILITASAN TERHADAP TEMAN SEBAYA DI SMP NEGERI 1 PONCOWARNO KABUPATEN KEBUMEN - Lolitha Tika Dewi Amelia; Nadira Rania Balqis (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Assertive Communication of Childrens with Disability to Peers in SMP Negeri 1 Poncowarno Kebumen Regency includes skills in assertive communication of demand, assertive communication of rejection, active communication plays a role in conversation, assertive communication of praise and assertive communication of self-expression. The research method used is descriptive research method with a qualitative approach. Sources of data used in this study are primary and secondary data sources. Data collection techniques used are in-depth interviews, observation and study documentation. The informants in this study were three children with disabilities, three peers and one teacher as the chief executive of the inclusive school. The results of assertive communication research of Childrens with Disability to peers in SMP Negeri 1 Poncowarno, Kebumen Regency, from the five aspects of assertiveness, it is known that the aspect of assertive communication plays a role in the conversation of childrens with disability towards peers is still lacking in its application in daily life, hereby the program is proposed "The Socialization Group in Improving Assertive Communication Skills Survived in Talking Childrens with Disability to Peers in SMP Negeri 1 Poncowarno Kebumen Regency". The social work method used is Social Group Work and the social work technique used is the socialization group.